2021
DOI: 10.2174/1566524020666200825163512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AnnexinA Group Translocated in Extracellular Vesicles on Tumorigenesis

Abstract: : Annexin, a calcium-dependent phospholipid binding protein, can affect tumor cell adhesion, proliferation, apoptosis, invasion and metastasis, as well as tumor neovascularization in different ways. Recent studies have shown that annexin exists not only as an intracellular protein in tumor cells, but also in different ways to be secret outside the cell as a “crosstalk” tool for tumor cells and tumor microenvironment, thus playing an important role in the development of tumors, such as participating in epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Importantly, lncRNAs affect cancer progression not only by functioning within cancer cells but also by affecting the TME (26). It is reported that TME constantly interact with the cancer cells to promote their progress via secretion of extracellular vesicles (33,34). In addition, cancer cells actively produce and release exosomes carrying lncRNAs to interact with various cells in the TME (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, lncRNAs affect cancer progression not only by functioning within cancer cells but also by affecting the TME (26). It is reported that TME constantly interact with the cancer cells to promote their progress via secretion of extracellular vesicles (33,34). In addition, cancer cells actively produce and release exosomes carrying lncRNAs to interact with various cells in the TME (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…This way, Anxs have been shown to play an important role in the development of tumours, e.g. by participating in epithelial-mesenchymal transition, regulating immune cell behaviour, and promoting neovascularisation [85].…”
Section: Discussionmentioning
confidence: 99%